Muslim Women Leadership: The Catalytic Style in Developing School Members' Psychological Well-Being Amidst Global Pandemic - Ummi Kultsum; Khamami Zada; Maya Defianty; Mumin Roup (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung in collaboration with Asosiasi Bimbingan dan Konseling Indonesia (ABKIN), 2022)
This article investigates how women principals practice their leadership to address the global pandemic challenges encountered by Islamic-based junior high schools or madrasah Tsanawiyah (MTs). The study examines the key behaviors and practices school leaders, particularly women, implement to address the global pandemic challenges. Some challenges in the global pandemic, including learning management, developing an online curriculum, school facilities, teacher performance, and school members' psychological well-being, were indicated to hinder the learning effectiveness in MTs. The MTs principals, the top-level leaders in the institutions, play a critical role in addressing these issues. This research utilized a multiple case study approach and collected qualitative data from six MTs in Bogor, Tangerang, and Bekasi. An in-depth interview with 18 participants was conducted to investigate the women's principal leadership practices. The findings revealed that principals displayed a catalytic leadership approach through an agent of change where school members and stakeholders are invited to change the curriculum system and performance to respond to the challenges of the global pandemic. The results of this study also indicate that most female principals prioritize the well-being of teachers and students in facing learning challenges in the pandemic era.